Oral HPV prevalence and its associations with HIV, oral health, immune function, and behavioral factors among youth and mothers in Nigeria: a cross-sectional study - Anil Kumar; Oluwaseun Peter; Esosa Osagie; Jianhong Chen; Paul Akhigbe; Jia Liu; Nosakhare Lawrence Idemudia; Peter Kavecky; Ozoemene Obuekwe; Fidelis Ewenitie Eki Udoko; Nicholas F. Schlecht; Yana Bromberg; et al. (BMC Public Health, 2026)
Abstract Background People living with HIV (PLWH) are more susceptible to human papilloma virus (HPV) infection; however, data on the oral HPV burden among youth with or without perinatal HIV exposure or infection in sub-Saharan Africa remain scarce. This study described the distribution of oral HPV and examined demographic, dental, immune and behavioral characteristics of youth and mothers across HIV exposure groups in Nigeria and explored characteristics that co-occurred with oral HPV DNA detection. Methods This baseline cross-sectional analysis leveraged data from a prospective cohort in Nigeria. At study enrollment, mothers were categorized as either HIV-infected (HI) or HIV-uninfected (HU), while youth participants were classified as HIV-infected (HI), HIV-exposed uninfected (HEU), or HIV-unexposed uninfected (HUU). Standardized questionnaires were used to capture behavioral data, and comprehensive dental examinations were used to assess decayed, missing, and filled teeth (DMFT), oral hygiene index simplified (OHIS), and gingival inflammation score (GIS). Oral rinse specimens were tested for oral HPV DNA and blood samples were collected for immune parameter assessment (CD4/CD8). The analysis was primarily descriptive given the small number of participants with oral HPV DNA detection. No inferential statistics were performed for HPV-stratified comparisons. Results In our study, the overall oral HPV prevalence was low and was detected in 7/671 (1%) youth and 8/404 (2%) mothers. Among youth, oral HPV DNA was predominantly detected in HI and HEU groups and exclusively among HI mothers. In descriptive comparisons, youth with HPV DNA tended to have higher CD4 and lower CD8 counts and differences in oral health indices, whereas mothers with HPV DNA reported earlier sexual debut and lower CD4 counts. No inferential statistics were applied to these subgroups. These observations are hypothesis-generating given the small number of participants with detectable HPV DNA. Conclusions Despite its low prevalence, oral HPV was detected predominantly among PLWH and co-occurred with certain dental and immunological characteristics in this small number of cases. These findings highlight oral health as a potential area of interest in the context of oral HPV DNA detection and support further investigation into the relationships among oral health, the immune response, and viral detection within the HIV care setting in sub-Saharan Africa but cannot establish causal or predictive relationships.